Metabolic engineering of Clostridium thermocellum for n-butanol production from cellulose - Liang Tian; Peter M. Conway; Nicholas D. Cervenka; Jingxuan Cui; Marybeth Maloney; Daniel G. Olson; Lee R. Lynd (Biotechnology for Biofuels, 2019)
Abstract Background Biofuel production from plant cell walls offers the potential for sustainable and economically attractive alternatives to petroleum-based products. In particular, Clostridium thermocellum is a promising host for consolidated bioprocessing (CBP) because of its strong native ability to ferment cellulose. Results We tested 12 different enzyme combinations to identify an n-butanol pathway with high titer and thermostability in C. thermocellum. The best producing strain contained the thiolase–hydroxybutyryl-CoA dehydrogenase–crotonase (Thl-Hbd-Crt) module from Thermoanaerobacter thermosaccharolyticum, the trans-enoyl-CoA reductase (Ter) enzyme from Spirochaeta thermophila and the butyraldehyde dehydrogenase and alcohol dehydrogenase (Bad-Bdh) module from Thermoanaerobacter sp. X514 and was able to produce 88 mg/L n-butanol. The key enzymes from this combination were further optimized by protein engineering. The Thl enzyme was engineered by introducing homologous mutations previously identified in Clostridium acetobutylicum. The Hbd and Ter enzymes were engineered for changes in cofactor specificity using the CSR-SALAD algorithm to guide the selection of mutations. The cofactor engineering of Hbd had the unexpected side effect of also increasing activity by 50-fold. Conclusions Here we report engineering C. thermocellum to produce n-butanol. Our initial pathway designs resulted in low levels (88 mg/L) of n-butanol production. By engineering the protein sequence of key enzymes in the pathway, we increased the n-butanol titer by 2.2-fold. We further increased n-butanol production by adding ethanol to the growth media. By combining all these improvements, the engineered strain was able to produce 357 mg/L of n-butanol from cellulose within 120 h.